Held Up - Radmann, Christopher (London Headline Review, 2012)
How far do you go to rescue your child? Paul van Niekirk, a successful white South African is held up at gun-point when driving his new BMW. He's dragged out and his abductor drives off in his car. It's an everyday car jacking. Except his nine-month old daughter is in the back seat. As a pacifist, Paul is reluctant to carry a gun, but he descends into the heart of darkness of his country determined to find his child. He uncovers a criminal gang involved in people trafficking and discovers in himself a capacity for violence. When the trail goes cold, he is on the verge of losing everything but finds redemption in the most unlikely circumstances
Keywords: South Africa -- South Africa--Johannesburg -- Human trafficking